Implementation of Character-Based Central Learning Program in Kindergarten al-Irsyad al-Islamiyyah Purwokerto - Novan Ardy Wiyani (International Journal of Emerging Issues in Early Childhood Education, 2019)
This research is naturalistic qualitative research aimed at describing the implementation of character-based learning center programs in kindergarten al-Irsyad al-Islamiyyah Purwokerto. The results showed that the implementation of learning centers carried out three main activities, namely the initial activities, opening activities, and core activities. In the core activities, three activities are carried out, namely the footing before playing, the footing when playing and the footing after playing. Internalization of character values in early childhood can be done both in the initial activities, opening activities, and core activities. Internalization of character values through center learning can be done optimally in the core activities. In stepping activities before playing children are introduced to the rules of the game that can make children have discipline. In the foothold when playing children play creatively and collaboratively according to the rules of the game. While in foothold activities after playing children are taught to be independent, namely by solving their problems and tidying up the toy equipment they use. The center learning program will be more effectively carried out to shape the character of students if it is accompanied by the implementation of habituation activities in the initial activities, opening activities, and final activities.DOI: http://doi.org/10.31098/ijeiece.v1i2.26